2016
DOI: 10.4103/0974-8237.193267
|View full text |Cite
|
Sign up to set email alerts
|

The role of transforaminal percutaneous endoscopic discectomy in lumbar disc herniations

Abstract: Objectives:To study 1)the efficacy of transforaminal percutaneous endoscopic lumbar discectomy in lumbar disc herniations.2) limitations and advantages of the surgical procedure. 3)morbidity and complications associated with the procedure.Materials and Methods:This study was carried out on 120 patients who had single level herniated disc Pre-operative assessment of VAS and MSS scoring systems were documented one day prior to surgery. Post operative results were determined by MacNab criteria and by modified Sue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Open discectomy is used as the main treatment of lumbar disc herniation, but the application of open discectomy is limited by the big surgical trauma and the incidence of postoperative complications including adhesions of nerve roots and lumbar instability (10). In order to reduce the damage of normal tissue caused by surgical operations and the incidence of postoperative complications, percutaneous endoscopic lumbar discectomy has been widely applied and is attracting increased attention.…”
Section: Discussionmentioning
confidence: 99%
“…Open discectomy is used as the main treatment of lumbar disc herniation, but the application of open discectomy is limited by the big surgical trauma and the incidence of postoperative complications including adhesions of nerve roots and lumbar instability (10). In order to reduce the damage of normal tissue caused by surgical operations and the incidence of postoperative complications, percutaneous endoscopic lumbar discectomy has been widely applied and is attracting increased attention.…”
Section: Discussionmentioning
confidence: 99%
“…Gotecha et al investigated the morbidity and was found in one other patient. Re-herniation of the intervertebral disc was also noted in 6 cases [18]. Wu et al emphasized on the difficulty of approach of L5-S1 level using FED.…”
Section: Resultsmentioning
confidence: 99%
“…The appropriate way to avoid this complication is the sufficient knowledge of clinical anatomy, especially for the inexperienced spine surgeon. After a pain-free period, the main problem is the re-herniation of the intervertebral disc [18]. The recurrence rate is similar to that of microdiscectomy and it ranges from 3 to 7% [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, minimally invasive spine surgery has been increasingly popular in treating LDH for multiple advantages compared with the open technique: such as less invasive, decreased blood loss, faster function recovery, shorter length of hospitalization, and lower risk of spinal instability [9][10][11].PETD via inside-and-out approach has become one of the most common minimally invasive spinal surgeries since Yeung et al developed the spinal endoscopic YESS system in 2002 [7,12].Many studies have indicated that this technique could achieve good results with effective nerve root decompression, low complication rates for most types of LDH [13][14][15][16]. Yeung et al [7] reported 307 cases of LDH treated with the this technique followed-up for more than one year, and the excellent -to -good rate was 89.3%.…”
Section: Discussionmentioning
confidence: 99%